2011
DOI: 10.1016/j.jip.2010.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Pathological effects of the microsporidium Nosema ceranae on honey bee queen physiology (Apis mellifera)

Abstract: Nosema ceranae, a microsporidian parasite originally described in the Asian honey bee Apis cerana, has recently been found to be cross-infective and to also parasitize the European honey bee Apis mellifera. Since this discovery, many studies have attempted to characterize the impact of this parasite in A. mellifera honey bees. Nosema species can infect all colony members, workers, drones and queens, but the pathological effects of this microsporidium has been mainly investigated in workers, despite the prime i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 55 publications
(64 reference statements)
3
80
2
1
Order By: Relevance
“…To our knowledge, TAC has thus far been measured only in homogenates of whole brood/ pupae and honeybee extracts (Farjan et al 2012(Farjan et al , 2014 or body segments (whole abdomens of honeybee queen (Alaux et al 2011), head and thorax of foragers and nurse (Williams et al 2008). The values of TAC measurements in whole-body homogenate or segments are limited because the specific origin of antioxidant protection cannot be defined.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, TAC has thus far been measured only in homogenates of whole brood/ pupae and honeybee extracts (Farjan et al 2012(Farjan et al , 2014 or body segments (whole abdomens of honeybee queen (Alaux et al 2011), head and thorax of foragers and nurse (Williams et al 2008). The values of TAC measurements in whole-body homogenate or segments are limited because the specific origin of antioxidant protection cannot be defined.…”
Section: Discussionmentioning
confidence: 99%
“…Although the queen is very susceptible to the disease, she may frequently remain immune to the infection in a diseased colony (Fyg, 1961), but the queens of colonies highly affected by the disease resulted in infection with spores too (Vecchi, 1972). In most cases, young queens are not capable of surviving a high level of Nosema (Alaux et al, 2011;Traver and Fell, 2012). The enterolith structure was first described by Fyg (1961), who also observed an accumulation of faeces and a considerable enlargement of the hind gut and stated that enterolithes are formed primarily on the rectal epithelium which the enteroliths are connected to by a short stalk.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the honey bee is an important model as several studies have reported the influence of parasites on bee behaviours. For example, parasites can induce an increase in resin collection at the colony level for potential self-medication (Simone-Finstrom and Spivak, 2012;Popova et al, 2014) and an alteration of pheromone production important in social communication Alaux et al, 2011). Immune stimulation alone (without the negative effect of parasites) can also modify social interaction Richard et al, 2012).…”
Section: Introductionmentioning
confidence: 99%